2013
DOI: 10.1063/1.4824477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of hole-transporting material for efficient and stable green phosphorescent organic light-emitting diodes

Abstract: We examined the hole-transporting-material (HTM)-dependent device characteristics of green phosphorescent organic light-emitting diodes (PHOLEDs) using an electron-transporting host. The emission efficiency of the PHOLEDs was proportional to the optical band gap and the triplet energy of the HTMs. On the other hand, the operational stability of the PHOLEDs was not proportional to the emission efficiency. By analyzing the device characteristics in relation to the molecular structure of HTMs, amine derivative wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In a previous study on HTMs, an amine derivative with dibenzothiophene such as DBTPB was found to be one of the promising HTMs for highly efficient and stable PHOLEDs; however, the E T of DBTPB is insufficient to confine the triplet exciton of green emitters . Thus, 4DBTPBD, 4DBTP3Q, and 4DBFP3Q were designed to enlarge the bandgap ( E g ) and E T compared with DBTPB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study on HTMs, an amine derivative with dibenzothiophene such as DBTPB was found to be one of the promising HTMs for highly efficient and stable PHOLEDs; however, the E T of DBTPB is insufficient to confine the triplet exciton of green emitters . Thus, 4DBTPBD, 4DBTP3Q, and 4DBFP3Q were designed to enlarge the bandgap ( E g ) and E T compared with DBTPB.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, ETMs with high E T have been intensively developed compared with HTMs. ,, As typified by 1,1-bis­[(4-ditolylamino) phenyl]­cyclohexane (TAPC) and 2,2′-bis­(3-ditolylaminophenyl)-1,1′-biphenyl (3DTAPBP), the HTMs that were developed many years ago are often used even in recent highly efficient OLEDs. ,, Since the stability of such phenylamine derivatives with high E T is poor, , the stability of the host/emitting materials has had to be evaluated in low-efficiency OLEDs using 4,4′-bis­[ N -(1-naphthyl)- N -phenyl-amino]­biphenyl (α-NPD). As has been noted, novel HTMs suitable for highly efficient and stable OLEDs had rarely been discussed until recently. In 2013, however, we first reported that the amine derivative with dibenzothiophene acts as an effective HTM suitable for an efficient and stable green PHOLED . However, the E T of the reported amine derivative, N 4, N 4′-bis­(dibenzo­[ b , d ]­thiophen-4-yl)- N 4, N 4′-diphenylbiphenyl-4,4′-diamine (DBTPB), is 2.35 eV, which is insufficient for confining completely the triplet exciton of green emitters.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, a molecular design strategy for HTMs suitable for efficient and stable green PHOLEDs was presented for the first time [12]. The typical HTMs reported until then had been phenylamine derivatives, although the HTM-dependent operational stability of OLEDs had never been discussed.…”
Section: Molecular Design For Hole Transportersmentioning
confidence: 99%
“…However, in recent years, the stability of OLEDs has begun to be intensively discussed from two viewpoints: operational stability and air-stability. Since high operational stability is essential for almost all OLEDs used for practical applications, there have been many reports on materials suitable for achieving operationally stable OLEDs [12][13][14][15][16][17][18][19][20][21][22][23]. Some OLEDs employing flexible substrates or simple encapsulation structures have been applied for optoelectronic sensors and biophotonics in recent years [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The PHOLED characteristics strongly depend not only on the host material but also on the EBL [6]. We compared the PHOLED characteristics using HTEB-2 and -NPD as the EBL.…”
Section: Htl-dependent Device Characteristicsmentioning
confidence: 99%